2018
DOI: 10.1111/ceo.13303
|View full text |Cite|
|
Sign up to set email alerts
|

Ocular coherence tomography‐measured changes over time in anterior chamber angle and diurnal intraocular pressure after laser iridotomy: IMPACT study

Abstract: LPI widened all angle sections with maximum effect observed in the site opposite the iridotomy. Angle changes were maintained up to 6 months after LPI treatment without any statistically significant change in DIOP fluctuation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…At 6 years, there was a significant difference in the rate of loss; however, it was small (0.74%), and the authors concluded that it was not clinically significant [266]. In another RCT involving primarily Chinese participants, the follow-up period was 3 years, which was shorter than the RCT; however, there was no significant difference in the rate of endothelial cell loss between the treated and untreated groups [268]. Based on these results, we concluded that although LPI treatment did not result in a clinically clear decrease in corneal endothelial cells, it may have affected the long-term course of the disease.…”
Section: Summary Of Sr Reportmentioning
confidence: 93%
See 1 more Smart Citation
“…At 6 years, there was a significant difference in the rate of loss; however, it was small (0.74%), and the authors concluded that it was not clinically significant [266]. In another RCT involving primarily Chinese participants, the follow-up period was 3 years, which was shorter than the RCT; however, there was no significant difference in the rate of endothelial cell loss between the treated and untreated groups [268]. Based on these results, we concluded that although LPI treatment did not result in a clinically clear decrease in corneal endothelial cells, it may have affected the long-term course of the disease.…”
Section: Summary Of Sr Reportmentioning
confidence: 93%
“…The literature related to an RCT from China called the ZAP trial, which compared PACS eyes with and without unilateral LPI treatment, included East Asians as in Japan, and had a long-term observation period of 6 years [265][266][267]. An RCT that followed corneal endothelial cell density for 3 years was also selected [268]. Another RCT, called the IMPACT study, was also selected; however, it was excluded from this CQ as it included both PACS and primary angle-closure, had a short observation period of 6 months, and included a Caucasian population [84].…”
Section: Process Of Recommendation Creationmentioning
confidence: 99%
“…Laser peripheral iridectomy (LPI) is one of the treatment options for angle closure because it can establish an outflow channel of aqueous humor and alleviate pupillary block [5][6] . After LPI, the iris becomes flat, and the angle of the chamber widens [7][8][9][10] . LPI is indispensable for glaucoma treatment [11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…The conventional method of treatment is the laser peripheral iridotomy (LPI) leading to an improvement in the topography of the anterior chamber angle (ACA)3,4 and to a decrease in intraocular pressure (IOP) fluctuations,5 which are considered a risk factor of glaucoma progression 6. Nevertheless, some authors do not note any improvement in hydrodynamics after LPI 7.…”
mentioning
confidence: 99%